2009
DOI: 10.1289/ehp.11647
|View full text |Cite
|
Sign up to set email alerts
|

One-Month Diesel Exhaust Inhalation Produces Hypertensive Gene Expression Pattern in Healthy Rats

Abstract: BackgroundExposure to diesel exhaust (DE) is linked to vasoconstriction, endothelial dysfunction, and myocardial ischemia in compromised individuals.ObjectiveWe hypothesized that DE inhalation would cause greater inflammation, hematologic alterations, and cardiac molecular impairment in spontaneously hypertensive (SH) rats than in healthy Wistar Kyoto (WKY) rats.Methods and resultsMale rats (12–14 weeks of age) were exposed to air or DE from a 30-kW Deutz engine at 500 or 2,000 μg/m3, 4 hr/day, 5 days/week for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
2
44
1
2
Order By: Relevance
“…Interestingly, there were no findings of pathological or inflammatory changes in the heart in that study. However, this diesel exposure was associated with marked inhibition of mitochondrial aconitase activity (indicative of oxidative stress) and genes involved in cardiac function, antioxidant compensation, and matrix metabolism (Gottipolu et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were no findings of pathological or inflammatory changes in the heart in that study. However, this diesel exposure was associated with marked inhibition of mitochondrial aconitase activity (indicative of oxidative stress) and genes involved in cardiac function, antioxidant compensation, and matrix metabolism (Gottipolu et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Koike et al (2002) analyzed rat alveolar macrophages that were exposed to DEP extract using the Atlas Rat Toxicology Array II and six genes, such as heme oxygenase 1, and thioredoxin peroxidase 2, were significantly elevated. Gottipolu et al (2009) Affymetrix rat 230A GeneChip arrays to analyze the left ventricular tissues of DE-exposed spontaneously hypertensive (SH) and Wistar Kyoto (WKY) rats and found 377 genes to be differentially expressed within the WKY rats and concluded that the hypertensive-like cardiac gene expression pattern was associated with mitochondrial oxidative stress. Saber et al (2009) used Agilent Mouse Oligo Microarrays (G4121A) and found expression changes in 6 genes, such as Serpina3c, Tmed3, and Apoe, in mouse liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice in the maternal stage when bloodbrain barrier (BBB) development is incomplete were exposed to DE in exposure chambers that contained fine particles and gases, and the results were measured by microarray technology. Microarray experiments have been used to research DE exposure effects on the lung, heart, and liver (Gottipolu et al, 2009;Koike et al, 2002;Saber et al, 2009). However, the brain is yet to be considered a target organ.…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos descrevem que após 24 horas da administração sistêmica em ratos (Nemmar et al, 2009) O efeito tanto inflamatório quanto sistêmico de que a inalação do material oriundo da combustão do diesel pode causar no sistema pulmonar, pode ser explicado pelo tamanho aerodinâmico das partículas, que são menores que 2,5 µm (Anselme et al, 2007;Gottipolu et al, 2009). Essas partículas têm a capacidade de atingir as regiões mais distais do pulmão, estimulando a liberação de citocinas pró-inflamatórias pelos macrófagos alveolares (Nemmar et al, 2002;Bayram et al, 1998) levando a diminuição da função pulmonar, agravamento de doenças respiratórias como asma e bronquite (Salvi et al, 1999;Sydbom et al, 2001).…”
Section: Análise Dos Hidrocarbonetos Policíclicos Aromáticosunclassified
“…Estudos recentes demonstraram que através da instilação intratraqueal aguda do PM 2,5 em ratos Wistar, na dose de 100 µg/mL e 500 µg/mL (Rivero et al, 2005a) e na dose de 50 µg/mL (Maatz et al, 2009) Em contrapartida, a literatura apresenta inúmeros estudos experimentais de toxicidade da queima do diesel (Campen et al, 2005;Anselme et al, 2007;Gottipolu et al, 2009;Saxena et al, 2009;Sunil et al, 2009) e de exposição controlada em humanos Lucking et al, 2008;Peretz et al, 2008aPeretz et al, , 2008bLangrish et al, 2009 Lucking et al, 2008;Langrish et al, 2009), a reatividade vascular (Peretz et al, 2008a) e a VFC (Peretz et al, 2008b). O compostos orgânicos da queima do diesel, são descritos como geradores de inflamação e estresse oxidativo (Ball et al, 2000;Saldiva et al, 2002;Nemmar et al, 2009;Sunil et al, 2009 Outros estudos também demonstraram que o B100 reduz as emissões de MP, CO e HC e aumenta as emissões de NO X (parâmetro não avaliado neste estudo) (EPA, 2002a;Graboski et al, 2003;Zou et al, 2003;Yuan et al, 2007;Lapuerta et al, 2008a).…”
Section: Análise Dos Hidrocarbonetos Policíclicos Aromáticosunclassified